2016
DOI: 10.1589/jpts.28.2778
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercises for breast cancer survivors: effects of 10 weeks of training on upper limb circumferences

Abstract: [Purpose] The aims of this study were to verify the effects on upper limb circumferences and total body extracellular water of 10 weeks of Nordic Walking (NW) and Walking (W), both alone and combined with a series of exercises created for breast cancer survivors, the ISA method. [Subjects and Methods] Twenty breast cancer survivors were randomly assigned to 4 different training groups and evaluated for upper limb circumferences, total body and extracellular water. [Results] The breast cancer survivors who perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The initial search resulted in the finding of 76 investigations. After reading the titles and the abstracts, 36 potential studies were identified, 9 of which were included in the final analysis (Figure ; Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Fields, Richardson, Hopkinson, & Fenlon, ; Fischer et al, ; Hanuszkiewicz, Malicka, Barczyk‐Pawelec, & Woźniewski, ; Hanuszkiewicz, Malicka, & Woźniewski, ; Jönsson & Johansson, , ; Malicka et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search resulted in the finding of 76 investigations. After reading the titles and the abstracts, 36 potential studies were identified, 9 of which were included in the final analysis (Figure ; Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Fields, Richardson, Hopkinson, & Fenlon, ; Fischer et al, ; Hanuszkiewicz, Malicka, Barczyk‐Pawelec, & Woźniewski, ; Hanuszkiewicz, Malicka, & Woźniewski, ; Jönsson & Johansson, , ; Malicka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of five investigations provided information about the effects of NW in lymphedemas (14,15,17–19 Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Jönsson & Johansson, ; Jönsson & Johansson, ; Malicka et al, ) Four of them returned significant positive effects after the exercise programme, which was manifested in a reduction of extracellular fluid (trivial to small ES) and the circumference of the arm (trivial to large ES) (Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ), as well as the lymphedema absolute volume (trivial ES) and lymphedema relative volume (trivial ES; Jönsson & Johansson, , ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations